(untitled) (Medical Forum Monthly, 2024)
Objective: The present study is aimed at exploring relationship between religious orientation and depression. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted out at Clinical Psychology, FG Post Graduate College Wah cantt from March 2011 to May 2011. Materials and Methods: The study included samples of 100 individuals from normal population of Wah Cantt. The educational level of participants ranged from intermediate level to post graduate. Religious orientation scale and Zung self rating scale of depression were used to measure the relationship between religious orientation and depression, Results: The present research project was designed to explore relationship between Religious Orientation and Depression. For this first of all Alpha reliability of religious orientation and depression scales were computed. Descriptive Statistics were measured for both scales. Conclusion: Our finding suggests that religious orientation is negatively correlated with depression